Pengaruh Kinerja Keuangan terhadap Return Saham Perusahaan Property dan Real Estate - Luvy Nurfinda Sari; Lintang Venusita (Universitas Negeri Surabaya, 2018)
The indicators that often be used as an analysis tool for measuring financial performance are EPS, ROE, and NPM, that measure performance reflecting the company's ability to generate profits and returns on investment firms. Saturated sample method used in this study using a sample of seventeen companies listed in Indonesia Stock Exchange. Hypothesis testing was performed by using the classical assumption test and linear regression analysis.The results of this study showed that the variable of economic value added, earnings per share, and net profit margin had no significant effect on the stock return of the property companies. Meanwhile, the variable of return on equity had a significant effect on the stock return of the property companies. Simultaneously, the analysis results suggested that the variable of economic value added, earnings per share, return on equity, and net profit margin had an influence to the stock returns of 11.9%, while the remaining of 88.1% can be influenced by other factors.